Evaluasi Kenyamanan Termal Ruang Sekolah SMA Negeri di Kota Padang - Lusi Susanti; Nike Aulia (Jurnal Optimasi Sistem Industri, 2013)
This research aims to determine thermal conditions and sensation of thermal comfort in classrooms of high schools in Padang. This study was conducted in 11 State Senior High School (SMA) represented 11 districts in Padang. About 10% of total student body in each schools were participated in this study to vote thermal comfort questioners. To determine thermal comfort level in this study, PMV (Predicted mean Vote) and PPD (Predicted Percentage of dissatisfied) method were used according to standard of thermal comfort in ASHRAE 55-2005 and ISO 7730. PMV method is used to determine scope of situation in the environment that scaled from +3 for very hot until -3 for very cold, and PPD is a method to calculate the number of human (in percentage) dissatisfied with the environment. Calculated PMV and PPD were compared with PMV and PPD resulted from individual vote from questionnaires. Result showed that in general, thermal conditions in classrooms had air temperature and radiant temperature from 27oC – 30oC, air humidity from 68% - 80%, and wind speed of 0 m/s. Calculated PMV from this condition were ranging from +1 slightly warm) until +2 (warm) while PPD calculated greater than 20%. Compared with calculated PMV and PPD values, the individual vote showed values from +0,5 (neutral) until +1 (slightly warm) while PPD values of individual vote greater than 20% except for SMA 2 and SMA 11 Padang. It is concluded that improvements of indoor thermal conditions have to make inside classrooms as well as landscape outside in order to improve thermal comfort level of students during learning and teaching.Keywords: Thermal Comfort, PMV (Predicted Mean Vote), PPD (Predicted Percentage ofDissatisfied), climatic factors, SMA